RELATIONSHIP BETWEEN IMMUNOLOGICAL STATUS AND ISCHEMIA, ECTOPIC MYOCARDIAL ACTIVITY IN PATIENTS WITH ANGINA PECTORIS - Bohdan, T.V.; Bogdan, V.V.; Sobol, V.O.; Biliachenko, I.V.; Moshkovska, Yu.O.; Tyravska, Yu.V. (World of Medicine and Biology, 2023)
The purpose of the study was to improve the diagnosis of stable angina and unstable angina by determining the correlations between the development of myocardial ischemia and cardiac arrhythmias with disorders of cellular and humoral immunity in patients with coronary artery disease. Using the obtained results, further optimize the treatment of patients with stable and unstable angina pectoris. It was determined that in the stable angina pectoris the development of painful myocardial ischemia depends on the level of CD4+ subpopulation (T-helpers) and circulating immune complexes, the development of painless myocardial ischemia depends on the level of CD4+ and CD8+ subpopulations (T-suppressors). Coronary artery disease destabilization and group ventricular extrasystoles are associated with elevated CD4+ subpopulations, CD8+ subpopulations and circulating immune complexes levels. Pathogenetic links between coronary circulatory disorders and ectopic myocardial activity with the development of imbalance of cellular and humoral immunity in patients with stable and unstable angina pectoris confirm the theory of immune inflammation as one of the pathogenetic links in the development of coronary artery disease and encourage studies and development of new drugs in antianginal therapy algorithms.
Keywords: stable angina pectoris; unstable angina pectoris; painful ischemia; painless ischemia; extrasystole; immunity